INCREASING INTEREST IN LEARNING ENGLISH IN ELEMENTARY SCHOOL STUDENTS THROUGH GUESSING VOCABULARY - Alfiani Alfiani; Muhammad Jafar; Dian Riani Said; Naimah Paronda (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2025)
English has become a very popular language today and has become an important need in the current era of globalization, including among elementary school students. However, students' interest in learning English is often very low and there is no motivation to learn English, including in rural areas. However, over time, English learning has spread to various remote areas or areas in elementary schools, including in rural areas. This community service article aims to increase interest in learning English in elementary school students, precisely at MIM Sawahan, Karakan Village, Weru District, Sukoharjo Regency through the vocabulary guessing method. The method used to increase interest in learning English is by using the tutoring method, which is a way or form of educational and teaching activities in the form of material about basic English that is in accordance with students' abilities and things related to their surroundings. Therefore, with this method, it is hoped that students can be more active and encourage their motivation and interest in the process of learning English. This vocabulary guessing method is a method or way of learning used in the teaching and learning process for students at school as well as an approach to students so that they can be active and motivated to learn English. In addition, this vocabulary guessing method is a method applied to students because it is easy to understand. The results of this activity show that there is an increase and development and interest of students in learning English. In addition, students experience an increase in mastery of new vocabulary and understanding of the vocabulary. Keywords: Learning, English, Interests, Students, Elementary School